MAC Protocol Design of Frequency Domain Contention Using of DM Subcarriers - Lee, Dong Gu; Kim, Jin Ki; Cho, Jun Woo; Kim, Jae Hyun (2019 16th IEEE Annual Consumer Communications and Networking Conference, CCNC 2019, 2019)
Time domain contention used in IEEE 802.11 has many overhead. To decrease the overhead, many frequency domain contention MAC protocols were proposed. However, to maximize the performance of system, the number of users who transmit data with a contention should increase. In this paper, we propose a subcarrier map broadcasting method. Access point (AP) broadcasts a subcarrier map including information about status of subcarriers. By broadcasting subcarrier map, more users can transmit data with a contention. We also propose the algorithm that changes the number of users who participate in a contention. The total throughput of the proposed MAC protocol with algorithm is not reduced while that without algorithm is reduced, as the number of users increases. We analyze total, uplink throughput of the proposed MAC protocol. We also compare throughput of the proposed MAC protocol between with and without algorithm. Mathematical analysis validate with simulation results. The proposed MAC protocol and algorithm improve throughput of system.
Keywords: Access points; Broadcasting methods; Frequency domains; MAC protocol; MAC protocol design; Mathematical analysis; Performance of systems; Subcarrier; Frequency domain contention; MAC protocol; OFDM subcarrier; Subcarrier map